A military history of South Africa from the Dutch-Khoi wars to the end of apartheid - Stapleton, Timothy Joseph 1967- (Praeger, 2010)
This book presents a narrative of armed conflict and the development of military establishments in the making of South Africa. The text not only concentrates on events that took place within what is now South Africa but also follows South African military personnel to other parts of Africa and the world